1980
DOI: 10.1029/rs015i003p00675
|View full text |Cite
|
Sign up to set email alerts
|

D region absorption effects during high‐power radio wave heating

Abstract: Simultaneous solutions of the differential equations governing electron energy and power flow are used to study D region absorption effects arising from high‐power HF heating. It is shown that self‐absorption of the heating wave can severely limit HF heating of the upper ionosphere and that the power density available for heating above the D region saturates as the heating power is increased. Models of the electron temperature distribution under heated conditions are used to compute the change in two‐way integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The HF heating component of the model is described in detail by Cohen et al [2010a] and builds off the work of Tomko et al [1980], Rodriguez [1994], Payne [2007], and Moore [2007]. To summarize, the three‐dimensional model uses a grid, which in this case is defined from 60–95 km in altitude and spans 160 km in each horizontal direction.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…The HF heating component of the model is described in detail by Cohen et al [2010a] and builds off the work of Tomko et al [1980], Rodriguez [1994], Payne [2007], and Moore [2007]. To summarize, the three‐dimensional model uses a grid, which in this case is defined from 60–95 km in altitude and spans 160 km in each horizontal direction.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…Getmantsev et al [1974] first showed that ionospheric heaters can generate ELF/VLF waves by periodically heating the ionosphere with high‐frequency (HF) radiation in the megahertz range. This heating modulates electron temperature in the D region ionosphere which leads to modulated conductivity and a time‐varying current at the modulation frequency (see Stubbe and Kopka [1977], Tomko et al [1980], and Ferraro et al [1982] for theoretical descriptions). While this method solves the problem of maintaining large antennas, the strength of the natural currents varies over time.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the absorption of wave energy approximately follows the 2‐D Gaussian distribution. Therefore, the energy flux of the incident wave can be expressed as [ Tomko et al ., ]. I(),rh=normalEnormalRnormalP4πh2normalexp()prefix−2truetrue∫h0hωcnormalInormalm()nnormaldhnormalexp()prefix−rr02true/σx2 where ERP is the effective radiated power of the radio wave, h 0 is the lower boundary of the ionosphere, r 0 = 0 is the center of the heating beam, and σ x is the radiate scale which can be expressed as σx=hrnormaltanφ2true/normalln2 where h r is the reflection height and ϕ is the half‐power width of the heating beam [ Kraus and Marhefka , ].…”
Section: Theoretical Modelmentioning
confidence: 99%